Effects of Non-Thermal Plasma on Germination, Root and Shoot Length of Tomato Seeds and Ginger Rhizome - Shivakumar, Neeta; Bagade, Nikita; Lal , Vignesh S; Rajanikanth, B S (Plant Tissue Culture and Biotechnology, 2025)
This study examines the effects of Dielectric Barrier Discharge using Non-thermal plasma treatment on the germination and growth of tomato (Solanum lycopersicum) seeds and ginger (Zingiber officinale) rhizomes. Given the environmental concerns over chemical fertilizers, plasma treatment presents a promising, sustainable alternative for enhancing seed germination and growth. Two types of Dielectric Barrier Discharge plasma-Surface Dielectric Barrier Discharge and Volume Dielectric Barrier Discharge were applied to the seeds and rhizomes, with germination rates, root, and shoot lengths assessed through daily observations. Statistical analysis revealed that plasma treatment significantly improved both germination and growth, with Volume Dielectric Barrier Discharge showing superior results compared to Surface Dielectric Barrier Discharge. Additionally, plasma treatment was more effective in breaking dormancy in ginger rhizomes than traditional methods. The findings suggest that plasma treatment can enhance seed germination, growth and dormancy breaking, providing a viable alternative to chemical treatments. Further research on plasma exposure parameters could optimize this method for broader agricultural applications, improving sustainability and crop productivity. Plant Tissue Cult. & Biotech. 34(2): 141-152, 2024 (December)